PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR ANAK DI TK ALIFIA SAMARINDA - Andi Aslindah (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research aims to know how teachers understand and awareness about the importance of utilizing the environment as a learning resource and to know how the teacher's strategy in implementing the environment as a medium and learning resources for the children in the Kindergarten Alifia. This study uses a qualitative method approach with a type of case study study. Case study research, concentrating intensively on one particular object that learns it as a case. From the results of the study get that: 1) teacher understanding of the importance of using the environment as a source of learning in early childhood is good enough. 2) before implementing the learning process that utilizes the environment as a learning resource, teachers need to prepare from the stage of activity planning, implementation of activities and follow up as an evaluation of the activities undertaken. 3) The constraints most often experienced by teachers during the implementation of learning by utilizing the environment as a learning resource is the time it takes to be longer and companion children who sometimes do not compare to the number of children.